2020
DOI: 10.3390/microorganisms8050694
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical and Microbiological Properties Are Changed by Long-Term Chemical Fertilizers That Limit Ecosystem Functioning

Abstract: Although the effects of fertilization and microbiota on plant growth have been widely studied, our understanding of the chemical fertilizers to alter soil chemical and microbiological properties in woody plants is still limited. The aim of the present study is to investigate the impact of long-term application of chemical fertilizers on chemical and microbiological properties of root-associated soils of walnut trees. The results show that soil organic matter (OM), pHkcl, total nitrogen (TN), nitrate-nitrogen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(52 citation statements)
references
References 87 publications
(94 reference statements)
4
47
0
1
Order By: Relevance
“…Our findings demonstrated that farming type led to a significant variation in the root microbiome structure, although the microbial alpha-diversity exhibited relatively low variability, and this effect could be influenced by the application of inorganic fertilizers. This was in line with previous findings in which long-term fertilization greatly influenced the root microbial community structure, although their microbial alpha-diversity was less impacted by different cropping systems (Hartman et al, 2018;Bai et al, 2020). The variation in microbial community structures may not necessarily influence microbial diversity or richness, as the changes in some taxonomic groups may be compensated by changes in other groups (Hartmann and Widmer, 2006).…”
Section: Root Microbial Community Composition Under Different Farming Practicessupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings demonstrated that farming type led to a significant variation in the root microbiome structure, although the microbial alpha-diversity exhibited relatively low variability, and this effect could be influenced by the application of inorganic fertilizers. This was in line with previous findings in which long-term fertilization greatly influenced the root microbial community structure, although their microbial alpha-diversity was less impacted by different cropping systems (Hartman et al, 2018;Bai et al, 2020). The variation in microbial community structures may not necessarily influence microbial diversity or richness, as the changes in some taxonomic groups may be compensated by changes in other groups (Hartmann and Widmer, 2006).…”
Section: Root Microbial Community Composition Under Different Farming Practicessupporting
confidence: 91%
“…Notably, the unfertilized nature farming soil was enriched for Proteobacteria, Firmicutes, Chloroflexi and Spirochaetes, whereas the fertilized conventional farming soil was enriched in Actinobacteria. Bai et al (2020) also reported that the phylum Proteobacteria was less diverse in the rhizosphere and root endosphere of walnut with the long-term use of chemical fertilizer, while Actinobacteria was enriched in these regions with fertilization. However, a study by Dai et al (2018) reported that the abundance of Proteobacteria was significantly increased in response to the addition of chemical fertilizer, which differs from our results.…”
Section: Root Microbial Community Composition Between Unfertilized Nature Farming and Fertilized Conventional Farmingmentioning
confidence: 93%
“…Monitoring the prevalence of tet(X), especially in the environment, is a priority considering its expanded substrate range, which poses a threat to human and animal health (59). To accurately characterize changes in ARGs with consistent manure applications, future studies should focus on longitudinal sampling (60). Further, recent research suggests that soil type, pH, and nutrient availability influence microbial compositional changes and ARGs in the environment (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been conducted regarding PGPR, BCA, and RNB and many effectors are known and are not mentioned in this review. Despite the knowledge of those secreted molecules, their functionality in planta remains unclear (Bai et al, 2020;Kumar and Dubey, 2020;Zhou et al, 2020). The importance of the RNB secretion system in nodule formation and symbiosis between rhizobia and legumes is known; however, direct interactions of effectors and plant proteins and the specific processes regulated by the effectors are not understood.…”
Section: Discussionmentioning
confidence: 99%